Constraints Faced By Beneficiary Under KCNM Programe in Karnataka - C. R. Motagi, Premlata Singh, V. Sangeetha, Sujit Sarkar, Satyapriya and Arpan (Indian Journal of Extension Education, 2023)
Green revolution transformed Indian agriculture by converting our nation from ship to mouth situation to self-sufficient country. With the record foodgrain production of 264.28 mt, paradoxically the malnutrition scenario in India is alarming. Almost one in six people are still not getting enough to eat on a daily basis. India's achievement in social sectors on alleviation of poverty, hunger and malnutrition, healthcare has been far from satisfactory. India is at the crossroads, the problem is not the availability of food, but access to right kind of food. Nutrition-sensitive agriculture needs to be emphasized. Karnataka Comprehensive Nutrition Mission is the program launched by Government of Karnataka in 2010 in selected high malnutrition burden districts of Karnataka. This is the first program based on a multi-sectoral approach with emphasis on agri-nutri linkages. Hence, it is essential to study the constraints of such programs for addressing malnutrition in a convergent, synergistic mode. Considering this the present study was undertaken with the objective of assessing the constraints of Karnataka Comprehensive Nutrition Mission Program as perceived by the beneficiaries and program officials. Shikaripura and Gubbi blocks from Shivamogga and Tumakuru districts respectively were selected purposively as the study locale, since the program was first initiated here. Eighty women beneficiaries who were involved in agriculture and forty program officials were finally selected as beneficiaries making the total sample size of 120. The ex-post facto research design was used. Appropriate descriptive and inferential statistical tools were used to analyze the data. Unavailability of bio-fortified seeds was the most severe constraint, along with rigid norms of the social system regarding food habits and a general negative attitude towards the Government programs. The credibility of the messages and convergence between various nutrition related programs were the most effective facilitating factors.